2013
DOI: 10.1063/1.4816248
|View full text |Cite
|
Sign up to set email alerts
|

Cold atomic beam ion source for focused ion beam applications

Abstract: Development and characterization of an iodine field emission ion source for focused ion beam applicationsHigh brightness inductively coupled plasma source for high current focused ion beam applications Performance of multicusp plasma ion source for focused ion beam applicationsWe report measurements and modeling of an ion source that is based on ionization of a laser-cooled atomic beam. We show a high brightness and a low energy spread, suitable for use in next-generation, high-resolution focused ion beam syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 26 publications
1
63
0
Order By: Relevance
“…The initial charge distributions were determined from the measured laser spatial profiles by calculation of the atomic excitation. For two-step ionization at a high 480-nm pulse energy, the probability of ionization is proportional to the probability of being in the intermediate 5P state before the 480-nm laser pulse 18,24,33 , but the usual expectations of saturation for a two-level transition 34 are not applicable since we must include loss via field ionization. Indeed, experimentally, we can infer the number of ions produced from the space-charge-induced bunch expansion ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial charge distributions were determined from the measured laser spatial profiles by calculation of the atomic excitation. For two-step ionization at a high 480-nm pulse energy, the probability of ionization is proportional to the probability of being in the intermediate 5P state before the 480-nm laser pulse 18,24,33 , but the usual expectations of saturation for a two-level transition 34 are not applicable since we must include loss via field ionization. Indeed, experimentally, we can infer the number of ions produced from the space-charge-induced bunch expansion ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pioneering work with cold atom sources has shown evidence of space-charge effects 21,22 , and the role of Coulomb interactions in cold ion beams has been studied in detail for continuous-mode low charge density operation [23][24][25] . In this paper we investigate space-charge effects in arbitrarily shaped nanosecond duration cold ion bunches produced by near-threshold photoionization of laser-cooled atoms.…”
mentioning
confidence: 99%
“…The advantage of using a Knudsen cell is that it can produce a very high flux of atoms (>10 13 s À1 at 400 K when using rubidium) as compared to a so called 2D þ MOT. 17 In the next stage, this beam is laser cooled and compressed in the two transverse directions. Simulations of this magneto-optical compressor (MOC) showed that this increases the flux density / of the beam to 4 Â 10 19 m À2 s À1 , while the transverse temperature T ?…”
Section: Source Designmentioning
confidence: 99%
“…This means that ion or electron sources based on cold atom ionization would be able to create at low acceleration energy very small focal spots with relatively strong currents. Focused ion beams have been generated starting from both a magneto-optical trap (MOT) [10,11] and a slow and cold atomic beam [12]. Their properties as nanoprobes have been demonstrated first with chromium [13] and then with lithium [14] ions, the latter reaching a 27 nm resolution at 2 keV energy and 1 pA current.…”
Section: Introductionmentioning
confidence: 99%